Carbon stock dynamics in biosphere reserves and mountainous forest ecosystems - Ermias Debie; Tesfaye Wasihun Abro (Trees, Forests and People)
Comprehensive knowledge of the spatiotemporal dynamics of carbon stocks and their drivers in biosphere reserves and mountainous ecosystems is crucial for developing successful conservation policies and programs. A synthesis of 63 studies reveals a mean decrease of 12.58 % in carbon stocks from 1975 to 2023 due to deforestation for agriculture and forest degradation. Effective policy intervention, enforcement, participatory forest restoration and management, fulfilling local communities’ socioeconomic needs, and sustainable agricultural practices are major to ensuring the sustainability of these ecosystems. The findings highlight the importance of adaptive management, community engagement, and innovative conservation strategies in enhancing carbon sequestration and resilience against climate change. These insights are valuable for policymakers, conservationists, and researchers aiming to balance ecological integrity with socioeconomic development.